Quranisme dalam Sorotan Tafsir Kontemporer: Analisis Kritis - Rifqi Baihaqi Zaki; Iqbal Hidayah (PT. Student Rihlah Indonesia, 2025)
The phenomenon of hadith rejection (Inkar al-Sunnah) promoted by the Quranism movement poses a serious challenge to the authenticity of Islamic teachings in the contemporary era. This study aims to examine the historical roots, key figures, and ideological structures shaping the worldview of Quranism, while offering a critique of its theological and epistemological implications. Employing a qualitative method with a literature review approach, the research analyzes the works of prominent figures such as Muhammad Tawfiq Sidqi, Rashad Khalifa, and Edip Yuksel, and applies Ziauddin Sardar’s framework of ideological critique. The findings reveal that the rejection of hadith is not merely a methodological error, but also threatens the epistemological foundations of Islam, undermines the authority of scholars, eliminates the principle of ijma‘ (consensus), and triggers interpretive relativism that could potentially divide the Muslim community. The novelty of this study lies in its focus on critiquing Quranism as an ideological movement rather than merely engaging in normative debate, thereby enriching the discourse on strategies to strengthen Islamic scholarly methodology. The implications of this research are expected to serve as a foundation for policymakers, educational institutions, and religious authorities in formulating preventive measures to counter the spread of ideas that may weaken the authority of Islamic sources.